Global Minimum Tax Implementation: Vietnam's Policy Recommendations - Le Thi Thao (Pancasila and Law Review, 2023)
Applying the global minimum tax rule creates an equal tax competition environment among countries today and limits the phenomena of tax evasion, tax avoidance, transfer pricing, and profit transfer. That is inevitable in the current integration and globalization environment. According to the plan, the application of the global minimum tax rule will start from January 1, 2024 in Vietnam. On the basis of legal analysis methods, statistical methods and practical law assessment from secondary document information, the views of experts analyzing the current situation of corporate income tax policy in Vietnam. in the south, preferential policies to attract investment, opportunities and challenges when applying the global minimum tax rule and the impact on the development and improvement of tax policies for foreign investors to ensure goals of attracting investment and sustainable development. The article discusses and analyzes the various challenges that countries are facing when imposing a global minimum tax. on the following aspects: (i) neutralization of tax incentive policies; (ii) the taxing rights of the investing country; (iii) competitiveness in attracting investment; (iv) recommend solutions for the Vietnamese government in law-making and effective enforcement in the coming time. This study using normative juridical, qualitative research methods on the basis of secondary literature information has analyzed the anticipated impact of the global minimum tax policy on Vietnam and the trend of building and perfecting legal policies, human, political, infrastructure, etc. tax and plan to gradually reform and internalize international commitments in the tax field in Vietnam.